Exploring Digital Multimodal Text in EFL Classroom: Transformed Practice in Multiliteracies Pedagogy - Yuslimu Ilmi; Pratiwi Retnaningdyah; Ahmad Munir (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study investigates EFL students’ composition of digital multimodal text. There were forty-four students recruited from tenth grade of a private senior high school in Sidoarjo. All of them were divided into seven groups and given authority to choose their own topic for the digital multimodal project; advertisement video. Based on the theory of multimodal analysis, this study examines both students’ processes and products. Qualitative case study was chosen as the design of the study and document analysis was chosen as the data collection technique. Through qualitative case study, the finding of this research shows that all the students’ groups used multimodal modes in creating their advertisement videos. Additionally, this study revealed that the qualities of the students’ project depend on two important things: the ability of the group members and the collaboration of the members in doing the project. Keywords: Multimodal Text, Multiliteracies Pedagogy, Transformed Practice, EFL Classroom, Senior High School.